1962
DOI: 10.1039/df9623400115
|View full text |Cite
|
Sign up to set email alerts
|

(H, H) coupling constants in the nuclear magnetic resonance spectra of hydrocarbon groupings

Abstract: The collected data on geminal (H, H) coupling constants in substituted methanes and ethanes show that this coupling constant in methane is negative in sign, relative to vicinal coupling constants; a reassessment of the theoretical situation is required.Vicinal (H, H) coupling constants in substituted ethanes and ethylenes are qualitatively well accounted for by Karplus' theoretical treatment ; the predicted positive sign is probably correct as it leads to a predominant -, +,pattern of sign-alternation for (H, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

1964
1964
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(36 citation statements)
references
References 13 publications
5
29
1
1
Order By: Relevance
“…1 is that the presence of the two chlorine atoms increases the coupling constants numerically by about 2 c/s. This is contrary t o what one expects since E dependencies of coupling constants so far published (11,(13)(14)(15)(16)(17) demand that J is inversely proportional t o E. I n the present case, however, the chlorine atoms are situated on a neighboring carbon, i.e. on a carbon bonded t o the carbons t o which the hydrogens are bonded.…”
Section: Trends For Jcis and Jttascontrasting
confidence: 54%
“…1 is that the presence of the two chlorine atoms increases the coupling constants numerically by about 2 c/s. This is contrary t o what one expects since E dependencies of coupling constants so far published (11,(13)(14)(15)(16)(17) demand that J is inversely proportional t o E. I n the present case, however, the chlorine atoms are situated on a neighboring carbon, i.e. on a carbon bonded t o the carbons t o which the hydrogens are bonded.…”
Section: Trends For Jcis and Jttascontrasting
confidence: 54%
“…The signs found for the ring-methyl proton couplings are in agreement wit11 the Dirac vector model ( 2 5 ) , more likely to be relevant to long range "through-bond" couplings (26). The simple molecular orbital calculation (4, 27) of the u-a interaction predicts negative values for JHqCt13' and JEI,cnln as we find, but JH,CE3m = 0.…”
Section: Discussionsupporting
confidence: 75%
“…ments have been reported linking the signs of ' J p p , 'JHp, 2 J H p , or 3JHp directly to that of l J = 1 3~. However, it has been shown that the signs of coupling constants across two bonds, 2J, are more variable than those for coupling across three bonds, 3J (30). The latter are norinally positive, certainly for the (H, H) case.…”
Section: ( B ) Tetramethyldiphosphine Disulphide (111): Jpp and Strumentioning
confidence: 87%
“…Recent work with the electric-field effect (29) has confirmed this hypothesis. Considerable progress has been made in placing the signs of (H, H ) coupling constants on this scale (30,31), but values for other situations are scarce. Consequently it is difficult to relate the signs of For personal use only.…”
Section: ( B ) Tetramethyldiphosphine Disulphide (111): Jpp and Strumentioning
confidence: 99%